A method for evaluating the quality stability of a vinyl caprolactam monomer raw material
By employing multi-point sampling and multi-dimensional index evaluation methods, the accuracy of evaluating the quality stability of vinylcaprolactam monomer raw materials was solved, enabling a comprehensive assessment of the uniformity within the container and the overall quality, thus avoiding misjudgment and risks in downstream applications.
Patent Information
- Application Number
- CN202611220748.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-11-06
AI Technical Summary
Existing technologies cannot accurately evaluate the overall quality stability and localized deterioration risk of barrelled vinylcaprolactam monomer raw materials, leading to misjudgments and downstream application problems.
After heating and melting the barrelled vinyl caprolactam monomer raw material using a multi-point sampling method, samples were taken from different vertical positions. The results were then comprehensively evaluated by combining appearance and color indicators, structural consistency indicators, and application simulation indicators. Thresholds and difference values were set to determine whether the product was qualified or unqualified.
It improves the accuracy and reliability of quality assessment, can identify the risk of localized deterioration, predict downstream application problems, provide practical and feasible disposal suggestions, and reduce the risk of unqualified raw materials flowing into the production process.
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical raw material quality evaluation technology, and more specifically, to a method for evaluating the quality stability of vinylcaprolactam monomer raw materials. Background Technology
[0002] Vinyl caprolactam (VCL) molecules contain both vinyl groups that can participate in free radical polymerization and a certain polar lactam ring structure. It has good reactivity, compatibility and the ability to improve the flexibility of cured films. It can be widely used as an active diluent or functional monomer in the field of UV-curable coatings, inks, adhesives and other photocurable materials.
[0003] VCL is a white to light yellow crystalline solid at room temperature with a melting point of approximately 35-38℃. Currently, commercially available VCL is mostly supplied in drums, with a common specification of 200kg / drum. Suppliers typically ship in a crystalline state, and users must heat and melt the entire drum of raw material to a liquid state before using it in production. Due to the influence of factors such as cooling rate, drum wall heat dissipation, and storage and transportation environment during the crystallization and melting process, the crystallization state and quality stability of the material at different locations within the drum may vary. During transportation and storage, drummed VCL typically undergoes prolonged storage and multiple environmental temperature changes, thus the raw material is exposed to a complex and variable thermal history, resulting in varying degrees of polymerization and deterioration.
[0004] Current technology for quality testing of VCL raw materials typically involves taking a single-point sample from the surface of the container while the raw material is still in a crystalline state. The quality is then determined based on conventional physicochemical indicators such as purity (HPLC), moisture content, platinum-cobalt color (APHA), refractive index, and viscosity. This method has several limitations. It should be noted that conventional sampling of drummed VCL raw materials usually only reflects the local state at the container opening. During long-term quality control, the applicant has found that after heating and melting, different sampling locations within the same container exhibit significant differences. The upper sample shows a relatively low platinum-cobalt color, while the lower sample shows a significantly increased color. Simultaneously, the matching degree between the infrared spectrum and the standard spectrum also decreases, indicating potential localized structural changes within the material. Judging solely based on single-point sampling at the container opening may not accurately reflect the overall state within the container, leading to misjudgments of raw materials with localized changes. Furthermore, existing quality evaluation systems mainly rely on conventional physicochemical indicators, which are mostly static parameters and may deviate from the actual performance of the raw material during subsequent processing. In practical applications, the applicant has found that while some batches of VCL raw materials meet the requirements of routine testing, phenomena such as gel particle formation and filtration system blockage may still occur during use in coating systems. This indicates that they may have latent polymerization tendencies or stability defects that are not identified by routine testing systems. Furthermore, current quality standards and inspection procedures do not systematically evaluate the internal homogeneity of the same batch of materials, meaning that raw materials with significant local performance differences may be misjudged as qualified products even when the average indicators are within acceptable limits. Therefore, how to provide a quality stability evaluation method suitable for crystalline or solid-state storage of vinylcaprolactam monomer raw materials, using representative multi-point sampling and combining multi-dimensional indicators such as structural consistency, appearance and color, and application simulation, to achieve a comprehensive evaluation of internal homogeneity, overall quality stability, and localized deterioration risk, has become a pressing technical problem to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a method for evaluating the quality stability of vinylcaprolactam monomer raw materials, which can comprehensively evaluate the overall quality stability and local deterioration risk of drummed vinylcaprolactam monomer raw materials, improve the accuracy and reliability of quality judgment, and provide a basis for raw material acceptance, storage and use.
[0006] To achieve the above objectives, this invention provides a method for evaluating the quality stability of vinylcaprolactam monomer raw materials, employing the following technical solution:
[0007] A method for evaluating the quality stability of vinylcaprolactam monomer raw materials includes the following steps:
[0008] S1. Sample pretreatment and multi-point sampling: After heating and melting the vinyl caprolactam monomer raw material in the barrel to be tested, use a sampler to take samples from different vertical positions inside the barrel to obtain samples from at least 3 different positions.
[0009] S2. Construct a multi-dimensional quality stability evaluation index system: For the samples obtained in step S1, detect at least one of the following: appearance and color index, structural consistency index, and application simulation index.
[0010] S3. Quality stability evaluation and judgment: Compare the test results of samples at each location with the preset threshold, and / or calculate the difference value between samples at each location. Based on the comparison results and / or difference values, determine whether the quality stability of the raw material in the barrel is qualified.
[0011] S4. Output evaluation results and handling suggestions: Output the judgment conclusion of "qualified" or "unqualified", and provide handling suggestions for those judged as unqualified.
[0012] Preferably, in step S1, the heating and melting temperature is 50-80℃, and the heating time is 24-96h, until the vinyl caprolactam monomer raw material in the barrel is completely converted into liquid.
[0013] Preferably, in step S1, the different vertical positions include the upper, middle and lower layers of the liquid raw material in the barrel; more preferably, the upper layer is 1 / 6 to 1 / 3 of the height below the upper liquid surface, the middle layer is 1 / 2 of the height inside the barrel, and the lower layer is 1 / 6 to 1 / 3 of the height above the bottom of the barrel.
[0014] Preferably, in step S1, after the vinyl caprolactam raw material is melted, a long tube sampler is used to vertically insert into the upper, middle, and lower layers of the barrel from the barrel opening to take samples.
[0015] Preferably, in step S2, the appearance and color indicators are selected from one or more of platinum cobalt colorimetry, Gardner colorimetry, Lab color space values, and color difference ΔECMC; the structural consistency indicators include one or more of high performance liquid chromatography purity and the degree of overlap between infrared spectroscopy and standard spectra.
[0016] Preferably, in step S2, the application simulation index is selected from one or more of gel permeation time, turbidity of cyclohexane dilution test, transparency of cyclohexane dilution test, and appearance of cyclohexane dilution test; wherein, the method for determining the gel permeation time is as follows: after uniformly mixing the vinylcaprolactam sample with an organic solvent, a photocurable resin, or a combination thereof that can dissolve the vinylcaprolactam sample at a preset mass ratio, the mixture is filtered through a standard filter, and the time required for the predetermined mass of the mixture to pass through the standard filter is recorded, or the filtration time or filtration volume corresponding to when the mixture begins to clog the standard filter is recorded, and these are used as evaluation parameters for gel permeation time.
[0017] Preferably, the organic solvent includes one or more of cyclohexane, ethyl acetate, and propylene glycol methyl ether acetate; the photocurable resin includes one or more of polyurethane acrylate resin, epoxy acrylate resin, and polyester acrylate resin.
[0018] Preferably, the mass ratio of the vinylcaprolactam sample to the organic solvent or photocurable resin is 1:(3-5); more preferably, the gel permeation time is determined at 20-30°C.
[0019] Preferably, in step S3, the preset thresholds include: platinum cobalt colorimetry ≤ 200 APHA is acceptable; and / or gel transmission time ≤ 22 seconds is acceptable; and / or infrared spectral overlap ≥ 99.95% is acceptable.
[0020] Preferably, in step S3, the criteria for determining the difference between samples at each location are as follows: if the difference in platinum-cobalt colorimetry between any two layers of the upper, middle, and lower samples is greater than 80 APHA; or the difference in gel transmission time between any two layers of the upper, middle, and lower samples is greater than 5 seconds; or the overlap of infrared spectra between any two layers of the upper, middle, and lower samples is less than 99.95%; then the uniformity of the raw material in the barrel is determined to be unqualified, and there is a risk of local deterioration.
[0021] Preferably, in step S3, the raw material in the barrel is deemed to have a serious risk of deterioration when the following conditions occur simultaneously: the platinum-cobalt colorimetry of the lower sample is >200 APHA, and the infrared spectrum overlap of the lower sample is ≤99.95%.
[0022] Preferably, in step S4, the disposal recommendations include one or more of the following: isolated storage, return to the supplier, downgraded use, and pretreatment before use; more preferably, the pretreatment includes one or more of the following: increasing filtration accuracy, shortening the filter replacement cycle, and purification treatment.
[0023] Preferably, the evaluation method is applicable to the quality stability evaluation of vinyl monomer raw materials that are stored in a crystalline or solid state at room temperature and require heating and melting before use.
[0024] Beneficial effects
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) This invention heats and melts the entire barrel of vinyl caprolactam monomer raw material, and then takes samples from different vertical positions at the top, middle and bottom of the barrel. This ensures that each sampling point is in a uniformly flowing liquid environment, avoiding the "point-to-surface" problem caused by chiseling the surface crystallization sample at the barrel opening. It can truly reflect the actual quality state of the material in different parts of the barrel, significantly improve the representativeness of the sampling and the authenticity of the test results, and fundamentally solve the technical defect of the existing single-point sampling method that easily misjudges locally deteriorated raw materials as qualified products.
[0027] (2) This invention constructs a multi-dimensional evaluation index system covering appearance and color indicators, structural consistency indicators, and application simulation indicators. The three types of indicators describe the quality of raw materials from different perspectives, such as the apparent state of the raw materials, the integrity of the molecular structure, and the actual performance in downstream applications. Compared with the existing technology that only relies on single static physicochemical indicators such as purity, moisture, and refractive index, it can more comprehensively and three-dimensionally reflect the true quality of the raw materials. Among them, the application simulation indicators (such as gel permeation time and cyclohexane dilution experiment) simulate the actual use environment of the raw materials in the downstream photocurable resin system. It can identify potential microgels or polymerization tendencies in the raw materials in advance, so that the test results can establish a direct correspondence with the downstream application performance. This makes up for the shortcomings of the existing physicochemical indicators and the risks of downstream applications being disconnected. It can effectively predict and avoid downstream application problems such as filter system blockage and gel particles in the cured coating caused by the hidden deterioration of the raw materials. Furthermore, the specific limitations on the type of solvent or photocurable resin, mixing mass ratio, measurement temperature, and standard filter pore size in the gel permeation time determination method ensure the controllability of the test conditions and the reproducibility of the results, making the test data between different batches and different laboratories comparable.
[0028] (3) This invention combines the evaluation of individual indicator thresholds with the evaluation of differences between samples at different locations. It can determine whether the quality of each sampling point meets the standards, and also identify whether there are abnormal fluctuations between different locations within the container. This overcomes the problem of existing technologies that only use single-point test results to represent the quality of the entire container, and may cause misjudgments due to average compliance masking local exceedances. It achieves a dual evaluation of the overall quality stability of the raw materials and the uniformity within the container. Based on this, this invention further sets up a classification judgment condition for severe deterioration risk, which can provide early warning and key identification for raw materials with more severe deterioration, making the quality judgment results hierarchical and facilitating users to take corresponding measures according to the risk level.
[0029] (4) Based on the evaluation results, this invention provides differentiated disposal suggestions such as isolated storage, return to the supplier, downgraded use, and pre-treatment before use (e.g., improving filtration accuracy, shortening filter replacement cycle, and purification treatment), forming a complete closed loop of detection, evaluation, decision-making, and disposal. This avoids the problem in existing technologies where there is a lack of clear disposal basis even if abnormalities are detected. It provides practical and feasible operational guidance for the acceptance, warehousing management, and production use of raw materials, helping to reduce product quality risks and economic losses caused by unqualified raw materials flowing into the production process. This method can be implemented using conventional laboratory testing equipment without the need for additional specialized and complex instruments. It has strong engineering feasibility and application value, and is also suitable for industrial quality inspection and supply chain quality control systems. Detailed Implementation
[0030] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0031] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the experimental materials used, unless otherwise specified, were all purchased from conventional biochemical reagent stores. All quantitative experiments in the following examples were performed in triplicate, and the data are the average of the three replicates or the average ± standard deviation.
[0032] I. Experimental Materials and Main Instruments
[0033] 1. Experimental Materials
[0034] Vinylcaprolactam monomer: Multiple batches of industrial-grade products, packaged in standard 200kg sealed drums;
[0035] Organic solvents: cyclohexane, ethyl acetate, and propylene glycol methyl ether acetate, all of analytical grade;
[0036] UV-curable resin: Polyurethane acrylate resin, industrial grade.
[0037] 2. Main Instruments
[0038] Electric heating drying oven, constant temperature water bath, stainless steel long tube sampler (inner diameter 8mm), platinum cobalt colorimeter, spectrophotometer, high performance liquid chromatograph (HPLC), Fourier transform infrared spectrometer (FTIR), gel permeation time measuring device, 200 mesh standard nylon filter.
[0039] II. Implementation Examples
[0040] Example 1: Evaluation of Intra-bucket Uniformity and Quality Stability Based on Colorimetric Indices
[0041] S1. Sample pretreatment and multi-point sampling
[0042] Take a 200kg barrel of vinylcaprolactam monomer with batch number A, place it in a 60℃ electric heating forced-air drying oven, ensuring air circulation around the barrel, and heat for 91 hours to confirm that the material inside the barrel is completely melted into a homogeneous liquid. Use a long tube sampler to vertically insert into the barrel from the opening and collect 100g samples at the following locations: 15cm below the liquid surface (upper layer, about 1 / 6 of the height below the liquid surface), 1 / 2 of the barrel height (middle layer), and 15cm above the bottom of the barrel (lower layer, about 1 / 6 of the height above the bottom of the barrel). These samples are numbered S1-upper, S1-middle, and S1-lower, respectively.
[0043] S2. Appearance and color index inspection
[0044] According to the standard method for determining platinum-cobalt colorimetry, the platinum-cobalt colorimetry of three samples was determined using a platinum-cobalt colorimeter. Each sample was measured in parallel three times, and the arithmetic mean was taken.
[0045] Test results: The upper layer sample has a platinum-cobalt color intensity of 100 APHA and appears as a light yellow clear liquid; the middle layer sample has a platinum-cobalt color intensity of 140 APHA and appears as a yellow clear liquid; the lower layer sample has a platinum-cobalt color intensity of 320 APHA and appears as a dark yellow liquid.
[0046] S3. Quality Stability Evaluation and Judgment
[0047] Single indicator threshold judgment: The platinum-cobalt color of the lower layer sample is 320 APHA, which is greater than the preset qualified threshold of 200 APHA, and the single indicator is unqualified.
[0048] Intra-bucket uniformity difference judgment: The platinum-cobalt color difference between the upper and lower samples is 220 APHA, which is greater than the preset difference threshold of 80 APHA. The intra-bucket uniformity is unqualified and there is a risk of local deterioration.
[0049] Based on the overall assessment, the raw material in this barrel was found to be substandard in terms of quality stability.
[0050] S4. Output evaluation results and handling recommendations
[0051] Conclusion: Unqualified;
[0052] Recommended action: Store in isolation and return to the supplier; do not use directly in production.
[0053] Example 2: Application Simulation Evaluation Based on Gel Permeation Time
[0054] S1. Sample pretreatment and multi-point sampling
[0055] Take a 200kg barrel of vinylcaprolactam monomer with batch number B, place it in a 55℃ electric heating forced-air drying oven, and heat it for 72 hours until the material is completely melted; according to the sampling method of Example 1, collect samples from the upper, middle and lower layers respectively, and number them as S2-upper, S2-middle and S2-lower.
[0056] S2. Application of simulated index detection (gel permeation time measurement)
[0057] Mix each sample with polyurethane acrylate resin at a mass ratio of 1:4, stir at 300 rpm for 5 minutes at 25°C until the system is homogeneous, take 200g of the mixture and add it to the gel permeation time measuring device, pass it through a 200-mesh standard filter at 0.1MPa, and record the time from the start of filtration until the filter becomes obviously clogged and the flow rate of the filtrate drops to one-tenth of the initial flow rate. This is the gel permeation time. Each sample is measured in parallel 3 times and the arithmetic mean is taken.
[0058] Test results: The gel permeation time for the upper layer sample was 15s; the gel permeation time for the middle layer sample was 18s; and the gel permeation time for the lower layer sample was 24s.
[0059] S3. Quality Stability Evaluation and Judgment
[0060] Single indicator threshold judgment: The gel permeation time of the lower layer sample is 24s, which is greater than the preset qualified threshold of 22s, and the single indicator is unqualified.
[0061] Uniformity difference determination within the barrel: The difference in gel permeation time between the upper and lower samples is 9s, which is greater than the preset difference threshold of 5s. The uniformity within the barrel is unqualified, and there is a risk of gel application in downstream applications.
[0062] Based on the overall assessment, the raw material in this barrel was found to be substandard in terms of quality stability.
[0063] S4. Output evaluation results and handling recommendations
[0064] Conclusion: Unqualified;
[0065] Recommendations: Downgrade the filter for use in non-critical applications; improve filtration accuracy and shorten filter replacement cycle before use.
[0066] Example 3: Structural Consistency Evaluation Based on Infrared Spectroscopy and Color Difference
[0067] S1. Sample pretreatment and multi-point sampling
[0068] Take 200 kg of vinyl caprolactam monomer in drums with batch number C, place it in a 65°C constant temperature water bath and heat for 48 hours until the material is completely melted; according to the sampling method of Example 1, collect samples from the upper and lower layers respectively, and number them as S3-upper and S3-lower.
[0069] S2. Structural consistency and color difference detection
[0070] Infrared spectroscopy detection: Sample preparation was performed using the liquid film method, with a scanning range of 4000-400 cm⁻¹. -1 4cm resolution -1 The number of scans was 32; the infrared spectrum of a qualified vinyl caprolactam standard was used as a reference, and the degree of overlap between the sample spectrum and the standard spectrum was calculated using the instrument's matching analysis software.
[0071] Color difference detection: A spectrophotometer is used, with D... 65 The Lab color space values of the samples were measured using a standard light source and a 10° field of view, and the color difference ΔECMC between the upper and lower samples was calculated.
[0072] Test results: The infrared spectrum overlap of the upper sample was 99.98%, with an L value of 96.7, an a value of -1.6, and a b value of 8.9; the infrared spectrum overlap of the lower sample was 99.89%, with an L value of 94.5, an a value of -1.2, and a b value of 12.3; the color difference ΔECMC between the upper and lower samples was 1.1.
[0073] S3. Quality Stability Evaluation and Judgment
[0074] Single indicator threshold judgment: The infrared spectrum overlap of the lower layer sample is 99.89%, which is lower than the preset qualified threshold of 99.95%. The single indicator is unqualified, indicating that the chemical structure of the lower layer sample has changed significantly.
[0075] Judgment of uniformity difference in the barrel: If the difference in the overlap of the infrared spectra of the upper and lower layers exceeds the allowable range, and the difference in b value is significant and ΔECMC exceeds the threshold that can be distinguished by the naked eye, the uniformity of color and structure in the barrel is not up to standard.
[0076] Based on the overall assessment, the raw material in this barrel was found to be substandard in terms of quality stability.
[0077] S4. Output evaluation results and handling recommendations
[0078] Conclusion: Unqualified;
[0079] Recommended disposal: Store in isolation. After purification and re-inspection, it can be downgraded for use in fields with lower requirements for appearance and optical performance.
[0080] Comparative Example 1
[0081] The conventional testing methods of existing technology were used for comparison: the same batch A barrel of vinyl caprolactam monomer used in Example 1 was taken, and without heating and melting treatment, the surface crystalline sample was directly chiseled out from the mouth of the barrel. The platinum cobalt color and gel transmission time were measured according to the methods of Example 1 and Example 2 respectively.
[0082] Test results: The platinum-cobalt colority of the surface sample at the bung of the drum is about 70 APHA; the gel penetration time is 14 s. Judged according to the conventional quality standards in the prior art, both indicators meet the qualification requirements, so the raw material quality of the drum is judged to be qualified;
[0083] Comparison conclusion: The traditional single-point sampling method can only reflect the state of the material on the surface layer at the bung of the drum, cannot identify the local deterioration problem in the lower layer inside the drum, has an obvious risk of missed detection, and is prone to misjudging raw materials with hidden quality hazards as qualified; the molten multi-point sampling method of the present invention can accurately identify local deterioration inside the drum, and effectively avoid quality misjudgment.
[0084] Comparative Example 2
[0085] Two drums of vinyl caprolactam monomer from the same production batch are taken, and heated and melted in different manners respectively:
[0086] Sample A: Heated in a constant-temperature water bath at 40°C for 24 h, with uniform heating;
[0087] Sample B: Heated in an electric hot-air drying oven at 73°C for 19 h, with strong local heating at the bottom of the drum.
[0088] After the materials in the two drums are completely melted, samples of the upper layer and the lower layer are collected respectively to detect the platinum-cobalt colority, Gardner colority and infrared spectrum coincidence degree, and the detection method is the same as that in the foregoing examples; the test results are shown in Table 1 below:
[0089] Table 1
[0090] sample Preprocessing methods Sampling location Platinum Cobalt Color APHA Gardner Chromaticity Infrared spectral overlap % Sample A water bath heating upper layer 100 1.5 99.98 Sample A water bath heating lower level 100 1.5 99.98 Sample B Oven heating upper layer 100 1.4 99.97 Sample B Oven heating lower level 320 4.7 99.89
[0091] Comparison conclusion: Water bath heating with uniform heating will not cause local quality difference inside the drum; while oven heating with non-uniform heating will cause local polymerization and deterioration of the material at the bottom of the drum. When the traditional single-point sampling method only takes the upper layer sample, it will misjudge Sample B as qualified; the multi-point layered evaluation method of the present invention can accurately identify the in-drum quality non-uniformity caused by thermal history and heating mode, and effectively evaluate the quality change of raw materials during storage, transportation and pretreatment processes.
[0092] The above content is merely examples and description made for the present invention. Various modifications or supplements made by those skilled in the art to the described specific embodiments or replacements in similar manners shall all fall within the protection scope of the present invention, as long as they do not deviate from the invention or exceed the scope defined by the appended claims.
Claims
1. A method for evaluating the quality stability of vinylcaprolactam monomer raw materials, characterized in that, Includes the following steps: S1. After heating and melting the vinyl caprolactam monomer raw material in the test barrel, take samples from different vertical positions inside the barrel to obtain at least three test samples from different positions. S2. Perform quality testing on each sample to be tested. The quality testing shall include at least one of the following: appearance and color indicators, structural consistency indicators, and application simulation indicators. S3. Compare the test results of each sample to be tested with the preset evaluation standard, and / or calculate the difference values of the corresponding test indicators between samples at different locations, so as to evaluate the quality stability and uniformity of the barrel-packaged vinyl caprolactam monomer raw material. S4. Based on the evaluation results of step S3, output the quality stability evaluation conclusion and provide disposal suggestions for the barrelled vinyl caprolactam monomer raw materials with unqualified evaluation results.
2. The quality stability evaluation method according to claim 1, characterized in that, In step S1, the heating and melting temperature is 50-80℃, and the heating time is 24-96h, until the vinyl caprolactam monomer raw material in the barrel is completely melted.
3. The quality stability evaluation method according to claim 1, characterized in that, In step S1, the different vertical positions include the upper, middle and lower layers of liquid raw materials in the barrel, and samples are taken from each layer using a long tube sampler.
4. The quality stability evaluation method according to claim 1, characterized in that, In step S2: the appearance and color indicators include one or more of platinum cobalt chromaticity, Gardner chromaticity, Lab color space value and color difference ΔECMC; the structural consistency indicators include one or more of high performance liquid chromatography purity, infrared spectrum and standard spectrum overlap; the application simulation indicators include one or more of gel permeation time, turbidity, transparency and appearance in cyclohexane dilution experiment.
5. The quality stability evaluation method according to claim 4, characterized in that, The method for determining gel permeation time includes: mixing a vinylcaprolactam sample with an organic solvent capable of dissolving vinylcaprolactam, a photocurable resin, or a combination of both at a preset mass ratio, filtering the mixture through a standard filter, recording the time required for a predetermined mass of the mixture to pass through the standard filter, or recording the filtration time or filtration volume corresponding to when the mixture begins to clog the standard filter, and using this as the gel permeation time.
6. The quality stability evaluation method according to claim 5, characterized in that, The organic solvent includes one or more of cyclohexane, ethyl acetate, and propylene glycol methyl ether acetate; the photocurable resin includes one or more of polyurethane acrylate resin, epoxy acrylate resin, and polyester acrylate resin.
7. The quality stability evaluation method according to claim 1, characterized in that, In step S3, the preset evaluation criteria include at least one of single-index threshold evaluation and evaluation of sample difference values at different locations.
8. The quality stability evaluation method according to claim 7, characterized in that, When the difference in platinum-cobalt color, the difference in gel transmission time, or the overlap of infrared spectra between any two layers of samples at different locations exceeds the preset allowable range, the uniformity within the container is deemed unqualified, and there is a risk of local deterioration.
9. The quality stability evaluation method according to claim 1, characterized in that, In step S4, the proposed disposal includes one or more of the following: isolated storage, return to the supplier, downgraded use, and pre-treatment before use.
10. The quality stability evaluation method according to any one of claims 1-9, characterized in that, The evaluation method is applicable to vinyl monomer raw materials that are stored in a crystalline or solid state at room temperature and require heating and melting before use.
